(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
Knowing an overview of the effectiveness on using WhatsApp application as an online learning media for mathematics subjects that will make it easier for teachers to choose and evaluate the use of learning media during learning activities from home due to the effect of Covid-19 pandemic was the main goal of this research. The population and sample of this research were all students who carry out mathematics learning activities online . The sample was selected using simple random sampling technique. The data collection instrument used an online learning questionnaire using the whatsapp application as a learning media. Data analysis used descriptive statistics. The results of the study obtained an overview of the effectiveness of online learning using the WhatsApp application which was assessed by students as very effective (7%), effective (81%), ineffective (6%) and very ineffective (6%).